Pengembangan Media Pembelajaran Lectora dalam Menelaah Struktur dan Kebahasaan Puisi Rakyat - Khoirul Muttaqin; Itznaniyah Umie Murniatie (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
This study aims to develop lectora learning media in studying the structure and language of folk poetry in seventh grade junior high school students. This study uses the Goll, Gall, and Borg R&D methods. The research data was collected through a questionnaire, unstructured interviews, documentation, and observation. This research data analysis utilizes Likert scale calculation. There are three validators in this research, namely media expert, graphic expert, and education practitioner. In addition, students also responded. A small scale trial was conducted on 7F grade Alizzah Batu junior high school students totaling 25 students. Then the usage test was carried out on 7E and 7G grade students totaling 53 students. From the results of the assessment from the instructional media material experts scored 3.01 or could be categorized as "feasible". Meanwhile, from the learning media graphic expert, the score was 3.53 or categorized as "very feasible". Next assessment given by education practitioners is 3.83 or categorized as "very feasible". Then the product was tested on 25 students. Of the ten questions given about the appearance and content of the media the average value obtained was 3.608 or categorized as "very feasible". After a little improvement was made again the trial use of class VII E and G as many as 53 students obtained an average value of 3.49 or categorized as "very feasible". Conclusion, this learning media is considered appropriate to be used, therefore, this learning media is classified according to the conditions in the classroom. Keywords: Learning Media, Lectora, People's Poetry